العلاقة السببية بين استهلاك الطاقة والناتج المحلي الإجمالي في عمان - Develi, Abdulkadir; Alsaeedi, Hosam (مجلة العلوم الإدارية و الإقتصادية, 2019)
This paper aimed to examine the relationship between Energy Consumption and Gross domestic product "GDP" in Oman, using annual logarithm data during the period 1971-2014, the results of Augmented Dickey Fuller "ADF", and Phillips, Perron "PP" stationarity tests showed that both Energy Consumption per capita and GDP per capita were stationary at the first order. Autoregressive-Distributed Lag "ARDL" model and Pairwise granger causality test, were applied, the results indicated that there’s bidirectional long run causality between energy consumption and GDP, and unidirectional short run causality running from GDP to energy consumption. Bidirectional long run causality indicates that increasing of GDP leads to a raise in energy consumption, and vice versa. this finding can help policy makers to develop appropriate policy related to energy consumption and GDP in Oman which has large amount of Oil, and natural gas reserves.